A primacy code for odor identity - Christopher D. Wilson (Nature Portfolio, 2017)
Odor identity remains stable despite changes in concentration yet the neural mechanisms are relatively unknown. Here the authors test a primacy coding model using an optogenetic masking paradigm in mice to show that a set of earliest activated receptors are sufficient to make decisions about odor identity across concentrations.